2014
DOI: 10.1161/circulationaha.114.010999
|View full text |Cite
|
Sign up to set email alerts
|

Central Sympathetic Inhibition to Reduce Postablation Atrial Fibrillation Recurrences in Hypertensive Patients

Abstract: The objective of this prospective, randomized, controlled study was to test the hypothesis that central sympathetic inhibition, using the centrally acting agent moxonidine, can lead to reduced postablation recurrence risk in patients with hypertension who are undergoing pulmonary vein isolation for drug-refractory paroxysmal AF.Background-The autonomic system is an important determinant of atrial arrhythmogenesis. Current evidence indicates that a combined sympathovagal drive is most commonly responsible for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 32 publications
0
10
0
4
Order By: Relevance
“…Moreover, moxonidine induced sympathetic inhibition decreased the AF burden in hypertensive patients with paroxysmal AF without any side effects (Deftereos et al, 2013). Furthermore, moxonidine reduced post-ablation recurrence of AF in hypertensive patients who underwent pulmonary vein isolation for drug-refractory paroxysmal AF (Giannopoulos et al, 2014).…”
Section: Sympatholytic Therapy – a Possible Strategy In The Managemenmentioning
confidence: 99%
“…Moreover, moxonidine induced sympathetic inhibition decreased the AF burden in hypertensive patients with paroxysmal AF without any side effects (Deftereos et al, 2013). Furthermore, moxonidine reduced post-ablation recurrence of AF in hypertensive patients who underwent pulmonary vein isolation for drug-refractory paroxysmal AF (Giannopoulos et al, 2014).…”
Section: Sympatholytic Therapy – a Possible Strategy In The Managemenmentioning
confidence: 99%
“…Initial results also suggest that antihypertensive therapies that modulate central sympathetic tone (moxonidine) reduce recurrent AF after catheter ablation. 31 Angiotensin converting enzyme inhibitors or sartans, while not effective in preventing recurrent AF in patients without structural heart disease in the short term, 32,33 may have long-term beneficial effects for the primary prevention of AF. 34 It has also been suggested that evidence-based therapy of heart failure with reduced ejection fraction can help to prevent AF.…”
Section: Prevention Of Recurrent Atrial Fibrillation In Patients Schementioning
confidence: 99%
“…LA remodelling leads to loss of normal sympathoinhibition; the resulting increase in autonomic activity to the LA can trigger AF, whereas restoration of central sympathetic inhibition ameliorates the risk of AF 16 . Heart failure also disrupts the adaptive neurohormonal response to LA stretch, such that chamber distension no longer leads to reflex sympathoinhibition, 16 but instead, causes paradoxical sympathetic activation, leading to AF 17 . In addition, circulating natriuretic peptides are increased in heart failure, particularly in patients with AF, but heart failure impairs the cleavage of prohormones in the LA, thus limiting the release of biologically active peptides 18 .…”
Section: Derangement Of Homoeostatic Functions Of the Left Atrium In mentioning
confidence: 99%